The molecular phylogenetics of Trachymyrmex Forel ants and their fungal cultivars provide insights into the origin and coevolutionary history of 'higher‐attine' ant agriculture. (3rd September 2019) - Solomon, Scott E.; Rabeling, Christian; Sosa‐Calvo, Jeffrey; Lopes, Cauê T.; Rodrigues, André; Vasconcelos, Heraldo L.; Bacci, Maurício; Mueller, Ulrich G.; Schultz, Ted R.
Abstract: The fungus‐growing ants and their fungal cultivars constitute a classic example of a mutualism that has led to complex coevolutionary dynamics spanning c . 55–65 Ma. Of the five agricultural systems practised by fungus‐growing ants, higher‐attine agriculture, of which leaf‐cutter agriculture is a derived subset, remains poorly understood despite its relevance to ecosystem function and human agriculture across the Neotropics and parts of North America. Among the ants practising higher‐attine agriculture, the genus Trachymyrmex Forel, as currently defined, shares most‐recent common ancestors with both the leaf‐cutter ants and the higher‐attine genera Sericomyrmex Mayr and Xerolitor Sosa‐Calvo et al . Although previous molecular‐phylogenetic studies have suggested that Trachymyrmex is a paraphyletic grade, until now insufficient taxon sampling has prevented a full investigation of the evolutionary history of this group and limited the possibility of resolving its taxonomy. Here we describe the results of phylogenetic analyses of 38 Trachymyrmex species, including 27 of the 49 described species and at least 11 new species, using four nuclear markers, as well as phylogenetic analyses of the fungi cultivated by 23 species of Trachymyrmex using two markers. We generated new genetic data for 112 ants (402 new gene sequences) and 95 fungi (153 new gene sequences). Our results corroborate previous findings that Trachymyrmex, as currently defined, is paraphyletic. We propose recognizing two new genera, Mycetomoellerius gen.n. and Paratrachymyrmex gen.n., and restricting the continued use of Trachymyrmex to the clade of nine largely North American species that contains the type species [ Trachymyrmex septentrionalis (McCook)] and that is the sister group of the leaf‐cutting ants. Our fungal cultivar phylogeny generally corroborates previously observed broad patterns of ant–fungus association, but it also reveals further violations of those patterns. Higher‐attine fungi are divided into two groups: (i) the single species Leucoagaricus gongylophorus (Möller); and (ii) its sister clade, consisting of multiple species, recently referred to as Leucoagaricus Singer 'clade B'. Our phylogeny indicates that, although most non‐leaf‐cutting higher‐attine ants typically cultivate species in clade B, some species cultivate L. gongylophorus, whereas still others cultivate fungi typically associated with lower‐attine agriculture. This indicates that the attine agricultural systems, which are currently defined by associations between ants and fungi, are not entirely congruent with ant and fungal phylogenies. They may, however, be correlated with as yet poorly understood biological traits of the ants and/or of their microbiomes. Abstract : Fungus‐farming ants cultivate fungus gardens for food. 'Higher' fungus‐farming ants, including the well‐known leaf‐cutting ants, cultivate domesticated cultivars that are clearly modified for life with ants. Here we show that the higher fungus‐farming ant genus Trachymyrmex consists of three different groups, one of which is the sister group of leaf‐cutting ants. We erect two new genera. We also produce a phylogeny of the higher fungi and show that it consists of multiple domesticated species cultivated by all three genera formerly placed in Trachymyrmex .